Correlation Analysis of Land Acquisition Regulation Policy for Public Interest with Regional Development and Financial Planning Regulations - Vebritha, Silvy; Trenggana, Widaningsih (Indonesian Scientific Publication, 2024)
Law enforcement in Indonesia faces challenges in addressing the rampant practice of prostitution, particularly involving service users and traditional commercial sex workers. Despite government efforts to reduce involvement in prostitution, the absence of specific regulations in Indonesian law has allowed users of these services to evade appropriate legal consequences. This research aims to highlight the urgency of criminalising both traditional commercial sex workers and their clients. The primary issue stems from economic factors, such as an individual's income or needs, particularly the difficulties faced by women in meeting their needs due to a lack of skills, which reduces their competitiveness in the job market. Additionally, there is a significant gap in the legal framework concerning regulation. This study employs a normative juridical method, utilising legislative, conceptual, and comparative approaches. The researchers analysed secondary legal materials, including local regulations from DKI Jakarta, Indramayu District, Tangerang City, Denpasar City, Badung Regency in Bali, Batam City, and Bandung Regency. Additionally, they examined Dutch regulations on brothels, specifically the